Infrared and Raman spectra of racemic ibuprofen sodium dihydrate – Spectra-structure correlations - Cvetkovska Bogatinovska, E.; Najkov, K.; Petrushevski, Gj.; Geskovski, N.; Koleva, V.; Stefov, V. (Elsevier BV, 2025)
Ibuprofen sodium dihydrate, a salt form of ibuprofen, is a widely used non-steroidal anti-inflammatory drug (NSAID) valued for its high solubility, which enhances absorption into blood plasma compared to standard ibuprofen. This study presents, for the first time, the infrared spectra of this compound and its deuterated analogues, recorded at room temperature (RT) and liquid nitrogen temperature (LNT). Additionally, room-temperature attenuated total reflectance (ATR) and Raman spectra were recorded. For the first time, spectral analyses and spectra-structure correlations for this compound were also conducted. Vibrational spectra were analyzed using factor group analysis. Comparison of RT and LNT infrared spectra of the protiated compound, as well as partially deuterated analogues, reveals that bands at 3340 cm-1, 3280 cm-1, and 3030 cm-1 correspond to HOH stretching vibrations, while a shoulder near 1580 cm-1 is attributed to HOH deformation modes. Bands at 901 cm-1, 827 cm-1, 749 cm-1, 607 cm-1, and 554 cm-1 in the LNT spectrum are linked to water librational modes. In the infrared spectrum of the slightly deuterated analogue (∼5% D) at RT, two new bands appear at 2477 cm-1 and ∼ 2325 cm-1. At LNT, three distinct bands are observed at 2479 cm-1, 2454 cm-1, and 2300 cm-1, suggesting the presence of a highly asymmetric water molecule in the structure. Unexpectedly, the spectra of the deuterated analogues lack bands associated with DOD deformation vibrations. Intense bands at 1547 cm-1 and 1415 cm-1 in the LNT spectrum are assigned to COO antisymmetric and symmetric stretching vibrations, respectively, while the band around 850 cm-1 is confidently attributed to γ(CH) vibrations.